Los efectos que causaría un medio de comunicación impreso para el desarrollo cultural de los habitantes en la cabecera cantonal de Alfredo Baquerizo Moreno (Jujan), Provincia del Guayas - Gomez Ayon, Sergio (2016)
The analysis of the media is a professional challenge. From this point we quote doers of communication science. They open up the range of visions since at times we can be alone with instrumentalism generated by the media. Rightly (Mattelart, A and Mattelart, M., 2003) states that the media set the tone for citizens on how they should be and how they should act providing features in the receiver on any given situation. Therefore, the functions of the media focus on social and psychological functions given in Chapters I and II to this dimension empowerment which can be used for private interests. The proposed Manage the Media Lab to assess whether the structure, shape and organization of the news media content circulating in Alfredo Baquerizo conform to the Communications Law, LOC., Acquires a dimension of novelty and feasibility because we would be dabbling as a venture journalistic work, which in this case is not limited to the size of seeking work in the media, which, faced with the reality that exists in the media is almost meritorious